Socializing Development Transnational Social Movement Advocacy and the Human Rights Accountability of Multilateral Development Banks (Edition 1) - Schettler, Leon Valentin (transcript Verlag, 2020)
As Multilateral Development Banks increasingly gained influence in shaping global development, transnational social movements pushed to hold them accountable for their human rights impact towards communities. Leon Valentin Schettler presents a novel causal mechanism of movement advocacy towards MDBs, combining disruptive and conventional tactics. Systematically comparing the evolution of human rights standards and complaint mechanisms over the last three decades, he reveals how the combination of 1) declining US hegemony, 2) counter-mobilization by China and 3) movement cooptation by the World Bank bureaucracy led to a dilution of human rights accountability in the 2010s.